SAT0364 History of digital ulcers in patients with systemic sclerosis is associated with peripheral vasculopathy as assessed by videocapillaroscopy and 22-mhz power doppler ultrasonography. (15th June 2017) - Schioppo, T; Orenti, A; Boracchi, P; Lucia, O De; Murgo, A; Meroni, PL; Ingegnoli, F; ,
Abstract : Background: Vasculopathy is considered a primary pathogenic event in systemic sclerosis (SSc) and it substantially contributes to prominent features of the disease such as digital ulcers (DUs). History of DUs (HDUs) has been shown to correlate with disease severity, new cardiovascular events, new DUs and overall poor prognosis [1]. Microvascular abnormalities as assessed by nailfold videocapillaroscopy (NVC) and power Doppler ultrasound (PDUS) have been demonstrated to be predictive of new DUs occurrence [2, 3]. Objectives: To study the severity of microvascular involvement at the 3rd and 4th finger of the dominant hand in patients with SSc with or without HDUs as assessed by NVC and 22-MHz PDUS. Methods: 100 SSc consecutive patients fulfilling the 2013 EULAR classification criteria were enrolled. PDUS was performed at the 3rd and 4th finger of the dominant hand after exclusion of ulnar artery occlusion (UAO). In case of UAO non-dominant hand was examined. Ultrasound investigation was performed with Esaote MyLab 70 XVG by means of linear array transducer (10–22 MHz). Power Doppler settings were standardized (Doppler frequency 14.3 MHz, Gain 55%, PRF 750 Hz). PDUS measurements included sagittal scan of nailbed and fingertip qualitatively graded from 1 (no signal) to 4 (marked hyperemia) [4], and resistivity index (RI) of ulnar and radial proper digital arteries. Capillary density (number/mm) was calculated by NVC with magnification 200X performed on two images of the same digits examined by PDUS. Results: 100 SSc patients, 87 (87%) women, 86 (86%) limited cutaneous SSc, median age 62.2 years old, median disease duration 8 years were evaluated. 7 (7%) patients had UAO. 33 (33%) had HDUs among them 23 had experienced more than one DUs and 2 had active DUs at the moment of evaluation. Semiquantitative perfusion score of sagittal scan of nailbed and fingertip were not significantly associated with the presence of HDU. RI and capillary density were significantly different in the two groups as shown in the table below: Conclusions: A significant lower RI of ulnar and radial proper digital arteries reported in patient with HDUs is novel. By contrast PDUS grading of nailfold and fingertip were not significantly different in patients with or without HDUs. The finding of a significant lower capillary number assed by NVC in patients with HDUs is consistent with previous results [2]. Adequately longitudinal studies exploring the predictive value of PDUS parameters are required to fully ascertain its role in SSc. References: Mihai C et al. Ann Rheum Dis. 2016;75(4):681–6. Cutolo M et al. Arthritis Rheumatol. 2016;68(10):2527–39. Lescoat A et al. Arthritis Care Res. 2016;Epub ahead of print. Newman JS et al. Radiology. 1996, 198:582–584. Disclosure of Interest: None declared